New Mitral Annuloplasty Ring Enables Oversizing of Transcatheter Heart Valve and Prevents Central or Paravalvular Leakage - Duerr, Georg Daniel; Sinning, Jan-Malte; Welz, Armin Georg; Mellert, Fritz (The Thoracic and Cardiovascular Surgeon, 2017)
Background Transcatheter valve-in-ring strategies have been developed to treat recurrent mitral regurgitation (MR) after failing surgical annuloplasty. However, suboptimal THV expansion with consecutive paravalvular leakage (PVL) is a procedure-immanent issue.Methods A rigid, saddle-shaped ring was cut at four locations. The segments were reconnected with pull-springs, rearranged to the original shape, and covered with a sewing cuff. The length of the annuloplasty ring construct, including extended pull-springs, was defined by the perimeter of an appropriate THV. We deployed a Sapien XT within the new ring, expanded it to its maximum extent, and investigated the geometrical changes.Results Fluoroscopy confirmed oval, saddle-shaped ring before dilation. After THV implantation, the ring segments spread apart and pull-springs were stretched. The extended ring changed its configuration from “oval” to “round” and anchored the THV leaving no paravalvular or central gaps as potential source for PVL.Conclusion We developed an expandable annuloplasty ring that is perfectly concerted to THV implantation. This proof-of-concept study revealed no PVL and good oversizing ability that might impact future annuloplasty ring design. Further studies have to evaluate durability and device safety.
Keywords: mitral valve disease; transcatheter aortic valve implantation; valvular heart disease; safety